A LITERARY REVIEW ON ROGANIDAN BY VAGBHATA: A CURSORY VIEW (AYUSHDHARA, 2017)
Vagbhata is one among the three classic writers of Ayurveda, along with Charaka and Sushruta. Vagbhata is believed to be writer of two important works Ashtanga Sangraha and the Ashtanga Hridaya The two texts straightforwardly acknowledge the strength of Samhitas of Caraka and Susruta and closely follow in the footsteps of the earlier masterpieces. Both these books are studied all over in India but they are more popular in South India. These texts are very popular till present era as they are easier to understand and contain essence of earlier treatises with original contribution. If we critically analyze the subject matter related to Ayurvedic diagnostics which has been added by Vagbhata then we will find that it forms important platform. This article deals mainly with the subject matter related to Ayurvedic diagnostics which has been added by the Vagbhata.Aims and Objectives: To enlighten the basic concept of framework of Nidana sthana to its full perspective and the importance to the specific concept as well as the number of chapter given in Nidana sthana. Materials and Methods: Astanga Sangraha and Astanga Hridaya are well known Ayurvedic compendium of post medieval period. These books were later on translated in many languages. For this present study multiple books have been referred. Causes of Roga utpati, Nidana as mentioned in different chapters of Astanga Hridaya, Astanga Sangraha have been screened and documented in a comprehensive manner under this study.CONCLUSION: Vagbhata felt need of compiling in one treatise all the eight branches of Ayurveda and so with this aim Astanga Sangraha and Astanga Hridaya was written. Diagnostics forms the very backbone of Ayurveda and without proper recognition of this branch we cannot treat patient properly.